Survival, Growth, and Reproduction: Comparison of Marbled Crayfish with Four Prominent Crayfish Invaders - Kouba, Antonín; Lipták, Boris; Kubec, Jan; Bláha, Martin; Veselý, Lukáš; Haubrock, Phillip J; Oficialdegui, Francisco J; Niksirat, Hamid; Patoka, Jiří; Buřič, Miloš (Biology, 2021)
Biological invasions are increasingly recognized ecological and economic threats to biodiversity and are projected to increase in the future. Introduced freshwater crayfish in particular are protruding invaders, exerting tremendous impacts on native biodiversity and ecosystem functioning, as exemplified by the North American spiny-cheek, signal and red swamp crayfish as well as the Australian common yabby. The marbled crayfish is among the most outstanding freshwater crayfish invaders due to its parthenogenetic reproduction combined with early maturation and high fecundity. As their introduced ranges expand, their sympatric populations become more frequent. The question of which species and under what circumstances will dominate in their introduced communities is of great interest to biodiversity conservation as it can offer valuable insights for understanding and prioritization of management efforts. In order to examine which of the aforementioned species may be more successful as an invader, we conducted a set of independent trials evaluating survival, growth, claw injury, and reproduction using single-species stocks (intraspecific interactions) and mixed stocks (interspecific interactions) of marbled crayfish vs. other crayfish invaders since the onset of exogenous feeding. In both single and mixed stocks, red swamp crayfish and yabby grew faster than marbled crayfish, while marbled crayfish were superior to both spiny-cheek and signal crayfish in terms of growth. With the exception of signal crayfish, the faster-growing species consistently reached a higher survival rate. The faster-growing species tended to negatively impair smaller counterparts by greater claw injury, delayed maturation, and reduced fecundity. Only marbled crayfish laid eggs as early as 14 weeks in this study, which is earlier than previously reported in the literature. Thus, the success of marbled crayfish among invasive crayfish is significantly driven by relatively fast growth as well as an early and frequent reproduction. These results shed light on how interactions between invasive populations can unfold when their expansion ranges overlap in the wild, thereby contributing to the knowledge base on the complex population dynamics between existing and emerging invasive species.
Keywords: biological invasion; species interactions; animal release; pet trade; sympatry